Development of finger rehabilitation device for post-stroke patient - Nor Rashekar, Binti Abdul Halim (Universiti Malaysia Sarawak, UNIMAS, 2010)
Finger plays one of the most important roles in human daily life. Disabilities of finger may affect human’s life to perform normal daily activities. There are several factors that contributing to the disabilities of human finger. Injured by accident, birth factor and physical disability since child also stroke leads to disabilities of finger. Stroke frequently happens to middle ages and above. Based on research conducted by the National Institute of Neurological Disorders and Stroke (NINDS), there are about more than 700,000 stroke patient over the world. Stroke patient needs to undergo rehabilitation exercise in order to recover the ability of the finger movements. Thus, rehabilitation device is needed to perform rehabilitation exercise. This project was carried out to design, develop and improvement of a robotic finger device. The design process involved only thumb, index and middle finger. The Autodesk Inventor 2008 software will be applied in the design.